PENGGUNAAN TEPUNG JEROAN IKAN CAKALANG TERHADAP PRODUKSI TELUR BURUNG PUYUH (Coturnix-coturnix japonica) - Andrian Nusi; Srisukmawati Zainudin; Fahria Datau (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
The purpose of the study was to determine the effect of giving skipjack viscera flour as a substitute for fish meal in the ration on the production of quail eggs. This research was conducted in September-October 2020, in Boidu Village, North Bulango District, Bone Bolango Regency, Gorontalo Province. The study used a completely randomized design (CRD) with 5 treatments and 4 replications. A total of 160 quails aged 47 days. The results showed that the provision of skipjack offal flour as a substitute for fish meal in the ration did not have a significant effect (P0.05) on the observed variables. Skipjack viscera flour can be used in quail rations as much as 12% in the ration.